Macrozoobenthoc Diversity on The Mangrove Ecosystem in The Gosong Telaga Selatan Mangrove Ecotourism, Singkil Utara District, Aceh Singkil District - Manik, Riau Wanshi; Barat, Welmar Olfan Basten; Sinaga, Mardame Pangihutan (Journal of Applied Geospatial Information, 2023)
Macrozoobenthos is a group of organisms that live in or on the surface of bottom sediments and have a length of more than 1 mm. One of the macrozoobenthos habitats is the mangrove ecosystem in the Gosong Telaga Selatan Ecotourism Mangrove, North Singkil District, Aceh Singkil Regency. Knowledge that macrozoobenthos can provide food availability for other organisms and as an indication of the suitability of potential water quality, especially pollution indicators, and plays an important role in the decomposition process of organic material in sediment in the mangrove ecosystem, so that the macrozoobenthos community can be used as an indicator of the balance of the mangrove ecosystem. This research aims to identify the diversity, uniformity, and dominance of Macrozoobenthos in the Gosong Telaga Selatan Mangrove Ecotourism Area, North Singkil District, Aceh Singkil Regency. This research uses a combination of two transect methods, namely line transects and quadratic transects. Determining the research location used the purposive sampling technique. Data analysis uses qualitative and quantitative analysis. The research results show that there are 7 Macrozoobenthos species, consisting of 3 classes, with a total of 182 individuals. Macrozoobenthic diversity in the ecosystem area in the Gosong Telaga Selatan Mangrove Ecotourism, North Singkil District, Aceh Singkil Regency is classified as moderate with a diversity index of Ĥ= 1.35-1.75, the uniformity index is classified as stable, ranging between E= 0.76-0.93, and the dominance index is classified as low.